Multidisciplinary Determination of the Phase Distribution for Vo X-Zro2-So42--Sepiolite Catalysts for Nh3-Scr - Gil-Llambias, F; Villarroel-Jorquera, M; Villarroel-Jorquera, M (2011)
A series of V2O5-ZrO2-SO4 2--sepiolite mixtures were extruded, calcined and characterised. NH3-SCR activity was found to be related to the content of the active VOX-ZrO2-SO42- phase (VSZ). The distribution of sepiolite and VSZ at the surface of the mechanical mixtures was studied by the electrophoretic migration technique. The samples were further characterised by nitrogen adsorption, NH3-TPD, XRD and scanning electron micrography techniques. The electrophoretic migration results showed that the addition of sepiolite to VSZ, by kneading in water, had a dramatic effect on the quantity of VOX-ZrO2-SO4 2- present at the support s surface, both strongly decreasing the molar fraction of zirconia at the surface, and altering the electrophoretic properties of the mixtures. The SEM micrographs, XRD patterns and activity measurements of the water-kneaded samples supported the electrophoretic migration results. Furthermore, it was verified by electrophoretic migration experiments that up until a composition of 75% VOX-ZrO 2-SO42-, the sepiolite fibers coats the zirconia particles. This has a slightly negative influence on the overall SCR activity of fresh catalysts. © 2011 Elsevier B.V. All rights reserved.